Collective behavior of thermally active colloids. - Golestanian, R (2012)
Colloids with patchy metal coating under laser irradiation could act as local heat sources and generate temperature gradients that could induce self-propulsion and interactions between them. The collective behavior of a dilute solution of such thermally active particles is studied using a stochastic formulation. It is found that when the Soret coefficient is positive, the system could be described in a stationary state by the nonlinear Poisson-Boltzmann equation and could adopt density profiles with significant depletion in the middle region when confined. For colloids with a negative Soret coefficient, the system can be described as a dissipative equivalent of a gravitational system. It is shown that in this case the thermally active colloidal solution could undergo an instability at a critical laser intensity, which has similarities to a supernova explosion.